Populisme Arya Wedakarna Sebagai DPD RI Dapil Bali - Fhanny, Putu; Bandiyah, Bandiyah; Pramana, Gede Indra (Jurnal Nawala Politika, 2020)
ABS TRACT   This study aims to find out how Arya Wedakarna's populism as DPD RI. This research framed using populism theory by Noam Gigron and Bart Bonikowski . The research uses qualitative descriptive method  with primary and secondary data usage, because it describes and illustrates phenomena that exist, both natural and human engineering, which pay more attention to the characteristics, quality, interrelationship between activities in relation to Arya Wedakarna's populism as DPD RI district of Bali. The results of this study are: first, Arya Wedakarna's populism can be seen through his ideology, discursive style, and the political strategy when becoming a member of the DPD. His populist identity appear through right-populism that applied in some of his anti-plural policies and statements, including religious tendencies and etnic issues . Second, Populism as political strategy then take the most dominant role in creating populist leader’s identity as a member of DPD RI   Keywords : Populism, Arya Wedakarna, DPD RI